1983
DOI: 10.1002/pd.1970030307
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐associated plasma protein A: A possible marker in the classification and prenatal diagnosis of Cornelia de Lange syndrome

Abstract: The concentration of human platelet lactogen (hPL), pregnancy specific beta-1 glycoprotein (SP-1) and pregnancy-associated plasma protein A (PAPP-A) were analysed in consecutive serum samples from a patient who gave birth to a child with Cornelia de Lange syndrome. HPL and SP-1 were present in normal concentrations from week 20 to week 35 of gestation whereas PAPP-A could not be detected in any of the samples examined. Immunohistochemical examination of two placentae from Cornelia de Lange syndrome revealed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 10 publications
2
42
0
Order By: Relevance
“…The use of maternal serum AFP, hCG, and uE 3 predicts 70% of fetuses diagnosed with trisomy 18. Low levels of uE 3 , less than or equal to 0.5 MoM, have been associated with adverse pregnancy outcomes: IUGR and early fetal loss. Levels less than 0.25 MoM are indicators that the fetus might be experiencing congenital adrenal hypoplasia, steroid sulfates deficiency, or Smith-Lemli-Opitz syndrome [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of maternal serum AFP, hCG, and uE 3 predicts 70% of fetuses diagnosed with trisomy 18. Low levels of uE 3 , less than or equal to 0.5 MoM, have been associated with adverse pregnancy outcomes: IUGR and early fetal loss. Levels less than 0.25 MoM are indicators that the fetus might be experiencing congenital adrenal hypoplasia, steroid sulfates deficiency, or Smith-Lemli-Opitz syndrome [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, low first and second trimester maternal serum pregnancy-associated plasma protein A (PAPP-A) have been associated with CdLs. The difficulty here is that PAPP-A measurements must be taken over a period of time, and PAPP-A is not a fetal analyte that is routinely measured in maternal serum during second trimester pregnancy screening tests [3,4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonsense, missense, frameshift and splicing mutations have all been identified, and severity is associated with presence of mutation and truncating lesions (Krantz et al, 2004;Tonkin et al, 2004 Prenatally, both large nuchal translucency and cystic hygroma have been reported in the first trimester ultrasound (Urban et al, 2001;Huang et al, 2002). Furthermore, cases with a low second trimester PAPP-A (below 0.20 MoM) were reported (Westergaard et al, 1983;Aitken et al, 1999) and Arbuzova et al (2003) reported a case with low PAPP-A detected at 11 weeks in a pregnancy that was terminated for multiple anomalies including growth retardation, limb reduction abnormalities, clubfoot and oligohydramnios, and on postmortem examination and mutation analysis of the NIPBL gene confirmed the diagnosis of CdLS. We report three cases of CdLS detected prenatally.…”
Section: Introductionmentioning
confidence: 99%
“…-The typical in utero facial profile of a fetus with CdLS, consisting of micrognathia, a prominent upper-lip, and a depressed nasal-bridge with somewhat anteverted nares [10][11][12]. -Maternal serum PAPP-A level may be low in the first and second trimester, if the fetus has CdLS [13][14][15].…”
Section: Prenatal Diagnosismentioning
confidence: 99%